2012
DOI: 10.17221/5850-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii and Neospora caninum antibodies in goats in the Czech Republic

Abstract: Toxoplasma gondii is zoonotic protozoan parasite that causes infections in many vertebrate species. The present study determined the seroprevalence of T. gondii and N. caninum in goats from the Czech Republic. Serum samples were collected from 251 healthy adult goats in the Czech Republic during the years 2006 to 2009. Sera samples were tested for serum antibodies to Toxoplasma gondii by an enzyme-linked immunosorbent assay with cut off equal to or higher than 50% S/P. The same samples were tested for serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
4
10
1
Order By: Relevance
“…The Neospora was reported at a prevalence of 3.3% and 6% in goats from Brazil and Czech Republic, respectively. Furthermore, 8.1% of sheep from Uberlandia, and 16.8% of sheep and 6.9% of goats from Greece showed seropositive for anti- N. caninum antibodies in a previous study [2, 12, 24]. The seroprevalence of N. caninum in sheep and goats obtained by us is similar with other reports from different countries.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The Neospora was reported at a prevalence of 3.3% and 6% in goats from Brazil and Czech Republic, respectively. Furthermore, 8.1% of sheep from Uberlandia, and 16.8% of sheep and 6.9% of goats from Greece showed seropositive for anti- N. caninum antibodies in a previous study [2, 12, 24]. The seroprevalence of N. caninum in sheep and goats obtained by us is similar with other reports from different countries.…”
supporting
confidence: 90%
“…N. caninum is the causative agent of neosporosis, an infection that always causes reproductive failure in cattle, sheep, goats and horses, and neurological alterations in dogs [1, 10, 26]. Numerous epidemiologic studies of toxoplasmosis and neosporosis have been reported in many areas worldwide [2, 6, 20, 27]. However, the epidemiological information about the seroprevalence of T. gondii and N. caninum is limited in Turkey [19].…”
mentioning
confidence: 99%
“…These results were obtained using ELISA. In the Czech Republic, the seroprevalence was reported to be 15 out of 251 (6.0%) using ELISA and the immunofluorescence antibody test (Bartova and Sedlak 2012). The prevalence in our present study was lower than that reported for other countries.…”
Section: Discussioncontrasting
confidence: 82%
“…In another survey from Poland only 0.47% of animals were Neospora-seropositive using an indirect ELISA method (Czopowicz et al 2011). In the neighboring Czech Republic, Bártová and Sedlák (2012) determined 25.0% seroprevalence using competitive ELISA.…”
Section: Discussionmentioning
confidence: 96%
“…Similar data were obtained in neighbouring countries. In the Czech Republic, Bártová and Sedlák (2012) recorded 66% seroprevalence in goats by latex-agglutination test against T. gondii, and in Austria it was more than 69% using the IFAT method (Edelhofer and Prossinger, unpublished data). The occurrence of toxoplasmosis in Europe ranges from sporadic outbreaks to the massive infection with clinical outcome in the herd (Antonis et al 1998;Masala et al 2003).…”
Section: Discussionmentioning
confidence: 99%